2012
DOI: 10.1152/ajpheart.00390.2012
|View full text |Cite
|
Sign up to set email alerts
|

Selective V1aagonism attenuates vascular dysfunction and fluid accumulation in ovine severe sepsis

Abstract: Vasopressin analogs are used as a supplement to norepinephrine in septic shock. The isolated effects of vasopressin agonists on sepsis-induced vascular dysfunction, however, remain controversial. Because V(2)-receptor stimulation induces vasodilation and procoagulant effects, a higher V(1a)- versus V(2)-receptor selectivity might be advantageous. We therefore hypothesized that a sole, titrated infusion of the selective V(1a)-agonist Phe(2)-Orn(8)-Vasotocin (POV) is more effective than the mixed V(1a)-/V(2)-ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 55 publications
(63 reference statements)
5
31
0
5
Order By: Relevance
“…Similar findings for the role of selective Via receptor agonism to those reported in the study by Maybauer et al (1) were noted in ovine models of fecal peritonitis and methicillinresistant Staphylococcus aureus pneumonia causing severe sep sis (11)(12)(13). In those studies, selective V ia agonism reduced fluid accumulation and norepinephrine requirements while increasing MAP, pulmonary gas exchange, and global oxygen transport (11).…”
supporting
confidence: 82%
“…Similar findings for the role of selective Via receptor agonism to those reported in the study by Maybauer et al (1) were noted in ovine models of fecal peritonitis and methicillinresistant Staphylococcus aureus pneumonia causing severe sep sis (11)(12)(13). In those studies, selective V ia agonism reduced fluid accumulation and norepinephrine requirements while increasing MAP, pulmonary gas exchange, and global oxygen transport (11).…”
supporting
confidence: 82%
“…More recently, we have studied the effects of POV versus AVP in our conscious ovine model of methicillin-resistant Staphylococcus aureus (MRSA) pneumonia-induced severe sepsis using the same fluid resuscitation and vasopressor titration protocol as in the present study (45). This model is characterized by a more severe vascular leak syndrome than the P. aeruginosa pneumonia-induced severe sepsis model studied here (46).…”
Section: Discussionmentioning
confidence: 99%
“…41 , 42 A similar fi nding has been noted in an experimental sepsis model. 43 Hence, although the cardiac output increases, vasodilatation occurs and the BP may remain unchanged. 41 Increased shear stress increases the expression of nitric oxide synthetase with increased release of nitric oxide.…”
Section: Fluid Therapymentioning
confidence: 99%
“…Myocardial edema due to excess fl uid administration compounds the myocardial dysfunction. 43 Evidence of the harmful effects of aggressive fl uid resuscitation on the outcome of sepsis is supported by experimental studies as well as by data accumulated from clinical trials. 43 , 56 Multiple clinical studies have demonstrated an independent association between an increasingly positive fl uid balance and increased mortality in patient with sepsis.…”
Section: Fluid Therapymentioning
confidence: 99%